v.1 - "Rao, C. Kameshwara" (Allahabad, 1994)
This book aims at placing before the practitioner a critical and analyatical exposition of the various principles of damages and compensation which help determine the exact measure of common law relief that may be awarded by court of law
Keywords: Damages and compensation-Law and legislation